EVALUATION OF THE PERSONAL INCOME PROGRESSIVE TAXATION AND THE SIZE OF TAX-EXEMPT AMOUNT IN LITHUANIA - Bikas, Egidijus; Subačienė, Rasa; Astrauskaitė, Ieva; Keliuotytė-Staniulėnienė, Greta (Ekonomika, 2014)
The tax systems of the European Union countries differ in many features. However, for taxing personal income, many EU countries use the method of progressive taxation. Progressive taxation is aimed to shift the tax burden from those with a relatively low income to those whose income is sufficiently high. Such personal income taxation system creates the prerequisites for social justice. In addition to different income tax rates, in a progressive tax system, a crucial role is played by the size of tax-exempt amount. In this article, personal income progressive taxation and the tax-exempt amount are analyzed as one of the progressive taxation tools. The study was conducted using the method of descriptive analysis as well as forecasting and modeling techniques.